The Influence of the Health Belief Model on the Decision to Get the COVID-19 Vaccine: An International Survey Study of College Students - Corinne Berger PhD; Uzi Ben-Shalom PhD; Zbyněk Tarant PhD; Joy Longo PhD; Michael DeDonno PhD (SAGE Publishing, 2023)
To better prepare for a potential future pandemic, it is important to investigate factors that influenced responses to the recent COVID-19 pandemic. The aim of the present study was to investigate factors that influenced the decision to get the COVID-19 vaccine. The COVID-19 pandemic has affected almost everyone throughout the world. Vaccines are a significant factor in managing a pandemic. As vaccines are developed, governments develop vaccine roll-out plans. Unfortunately, vaccine hesitancies can slow the implementation of any vaccine program. A question arises as to the factors that are associated with the decision to get vaccinated. The present study explored associations between vaccine hesitancy, and the Health Belief Model (HBM) in student samples from the Czech Republic, Israel, and the United States. From August, 2021 through December, 2021, an online survey was distributed in Czech, Hebrew, and English. A total of 447 participants completed the survey. A binomial logistic regression was conducted to ascertain the influence of perceived susceptibility, severity, benefits, and barriers on the likelihood that participants are vaccinated. Results revealed that the factors of perceived severity and perceived benefits explained 52.6% (Nagelkerke R 2 ) of the variance in vaccination. An analysis of Variance (ANOVA) found significant differences between countries for the 4 HBM factors. Based on these findings, it is recommended that policymakers put forth added emphasis on the severity of a virus and the benefits associated with the vaccine. Further, since there appears to be variability between countries in perceptions of the virus, and associated vaccine, governments should consider factors within their own environment when developing a strategy to combat a pandemic. More specifically, government could explore their own strengths, weaknesses, opportunities, and threats as they develop a pandemic strategy. Additional practical and theoretical implications are discussed.